Refeeding Syndrome in a 5 Years Old Child - Rifayatullah Afridi; Aneela Ambreen; Faizan Ali Janjua; Muhammad Riaz Khan (Journal of Gandhara Medical and Dental Sciences, 2017)
Refeeding syndrome is a rare but preventable complication of malnutrition management. This is the second case of refeeding syndrome being reported from Pakistan. Although many cases have been reported worldwide. It is a clear indication of lack of knowledge of the entity (Refeeding syndrome) in our doctor’s community. Refeeding syndrome presents with a mix picture of clinical manifestations and thus it is necessary to keep a regular check and balance of electrolyte disturbance especially serum phosphate levels before and after initiating nutrition irrespective of the route nutrition are given through. We are reporting a case of refeeding syndrome in a severely malnourished 5-year-old child which unfortunately died despite taking strict lifesaving actions.